Biases from Oxford Nanopore library preparation kits and their effects on microbiome and genome analysis - Ziming Chen; Chian Teng Ong; Loan To Nguyen; Harrison J. Lamb; O. González-Recio; M. Gutiérrez-Rivas; Sarah J. Meale; Elizabeth M. Ross (BMC Genomics)
Abstract Background Oxford Nanopore sequencing is a long-read sequencing technology that does not rely on a polymerase to generate sequence data. Sequencing library preparation methods used in Oxford Nanopore sequencing rely on the addition of a motor protein bound to an adapter sequence, which is added either using ligation-based methods (ligation sequencing kit), or transposase-based methods (rapid sequencing kit). However, these methods have enzymatic steps that may be susceptible to motif bias, including the underrepresentation of adenine-thymine (AT) sequences due to ligation and biases from transposases. This study aimed to compare the recognition motif and relative interaction frequencies of these library preparation methods and assess their effects on relative sequencing coverage, microbiome, and methylation profiles. The impacts of DNA extraction kits and basecalling models on microbiome analysis were also investigated. Results By using sequencing data generated by the ligation and rapid library kits, we identified the recognition motif (5’-TATGA-3’) consistent with MuA transposase in the rapid kit and low frequencies of AT in the sequence terminus of the ligation kit. The rapid kit showed reduced yield in regions with 40–70% guanine-cytosine (GC) contents, while the ligation kit showed relatively even coverage distribution in areas with various GC contents. Due to longer reads, ligation kits showed increased taxonomic classification efficiency compared to the rapid protocols. Rumen microbial profile at different taxonomic levels and mock community profile showed significant variation due to the library preparation method used. The ligation kit outperformed the rapid kit in subsequent bacterial DNA methylation statistics, although there were no significant differences. Conclusions Our findings indicated that careful and consistent library preparation method selection is essential for quantitative methods such as bovine-related microbiome analysis due to the systematic bias induced by the enzymatic reactions in Oxford Nanopore library preparation.